HOW PRODUCT QUALITY AND BRAND AMBASSADORS DRIVE PURCHASE DECISIONS THROUGH BRAND TRUST TOWARD BADMINTON RACKETS - Alvindy, Alvindy; Keni , Keni (Graduate Program of Universitas Tarumanagara, 2025)
Badminton, as a highly regarded sport in Indonesia, has increased the public’s interest to play and thereby created opportunities for badminton’s equipment companies. However, the competition between those companies has been very dense as they offer similar products which are purchased with low frequency by customers. Therefore, it is essential for the companies to examine factors that can affect customers’ decision to purchase the equipment. This study aims to analyze the influence of brand ambassadors and product quality on purchase decisions for badminton rackets, with brand trust as a mediating variable. Data collection was conducted online by using Google Forms, employing a convenience sampling technique. The respondents comprise of 198 consumers who own and use badminton rackets. The data were analyzed by using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) method, by utilizing the SmartPLS4 software. The results revealed that brand ambassadors have a significant and positive impact on brand trust but do not directly influence purchase decisions. In contrast, product quality significantly and positively affects brand trust and purchase decisions. Furthermore, brand trust was found to mediate the influence of brand ambassadors and product quality on purchase decisions. The findings of this study underline the crucial role of brand trust in enhancing consumer’s purchase decisions. Additionally, superior product quality emerged as a more dominant factor that influence purchase decisions compared to brand ambassadors. These insights highlight the importance of prioritizing product quality and leveraging brand trust as a strategic focus for companies to drive consumer’s purchase decision effectively.